PROJECT EDUCATION AS A PRACTICAL-TECHNOLOGICAL SYSTEM OF DEVELOPING SOCIAL COMPETENCE IN FUTURE SOCIOLOGISTS (Scientific journal of the Fergana State University, 2024)
The development of the social competence of the future sociologist as a experienced specialist should help young people find their place in the workforce, receive a quality education, form interpersonal social and cultural dialogue, but most importantly, make the individual responsive. Its development at the level and creation of the necessary conditions for realizing its potential is an urgent task. For this reason, the article analyzes the practical and technological system for developing the social competencies of a future sociologist on the basis of project-based education.